Snf2h-mediated chromatin organization and histone H1 dynamics govern cerebellar morphogenesis and neural maturation - Alvarez-Saavedra, Matías; De Repentigny, Yves; Lagali, Pamela S; Raghu Ram, Edupuganti V S; Yan, Keqin; Hashem, Emile; Ivanochko, Danton; Huh, Michael S; Yang, Doo; Mears, Alan J; Todd, Matthew A M; Corcoran, Chelsea P; et al. (Nature communications, 2014)
Chromatin compaction mediates progenitor to post-mitotic cell transitions and modulates gene expression programs, yet the mechanisms are poorly defined. Snf2h and Snf2l are ATP-dependent chromatin remodelling proteins that assemble, reposition and space nucleosomes, and are robustly expressed in the brain. Here we show that mice conditionally inactivated for Snf2h in neural progenitors have reduced levels of histone H1 and H2A variants that compromise chromatin fluidity and transcriptional programs within the developing cerebellum. Disorganized chromatin limits Purkinje and granule neuron progenitor expansion, resulting in abnormal post-natal foliation, while deregulated transcriptional programs contribute to altered neural maturation, motor dysfunction and death. However, mice survive to young adulthood, in part from Snf2l compensation that restores Engrailed-1 expression. Similarly, Purkinje-specific Snf2h ablation affects chromatin ultrastructure and dendritic arborization, but alters cognitive skills rather than motor control. Our studies reveal that Snf2h controls chromatin organization and histone H1 dynamics for the establishment of gene expression programs underlying cerebellar morphogenesis and neural maturation.
Keywords: indoly; Cerebellum; mikročipová analýza; Bromodeoxyuridine; chromozomální proteiny, nehistonové; Indoles; Mice, Transgenic; histony; adenosintrifosfatasy; metoda rotující tyčky; In Situ Hybridization; koncové značení zlomů DNA in situ; hybridizace in situ; Microarray Analysis; Female; Rotarod Performance Test; analýza rozptylu; In Situ Nick-End Labeling; myši transgenní; Purkyňovy buňky; polymerázová řetězová reakce s reverzní transkripcí; Analysis of Variance; Blotting, Western; Neural Stem Cells; Tolonium Chloride; Galactosides; Reverse Transcriptase Polymerase Chain Reaction; zvířata; Homeodomain Proteins; myši; Immunohistochemistry; počítačové zpracování obrazu; imunohistochemie; Fluorescence; Image Processing, Computer-Assisted; Mice; Morphogenesis; Chromosomal Proteins, Non-Histone; Gene Expression Regulation, Developmental; nervové kmenové buňky; bromodeoxyuridin; morfogeneze; Adenosine Triphosphatases; ženské pohlaví; restrukturace chromatinu; Male; Histones; homeodoménové proteiny; Chromatin Assembly and Disassembly; toloniumchlorid; transmisní elektronová mikroskopie; Real-Time Polymerase Chain Reaction; mozeček; Microscopy, Electron, Transmission; fluorescence; vývojová regulace genové exprese; Animals; western blotting; galaktosidy; mužské pohlaví; chromatinová imunoprecipitace; Chromatin Immunoprecipitation; kvantitativní polymerázová řetězová reakce; Purkinje Cells